2019
DOI: 10.1039/c8cp05870a
|View full text |Cite
|
Sign up to set email alerts
|

Double-zigzag boron chain-enhanced Vickers hardness and manganese bilayers-induced high d-electron mobility in Mn3B4

Abstract: The D7b-type structure Mn3B4 was fabricated by high-temperature and high-pressure (HPHT) methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Hard and superhard materials (≥40 GPa) are very important industrial materials, which are widely used in various industrial applications because of their high hardness, ultracompressibility, high melting point, and excellent thermal stability etc . In comparison to diamond and boron nitride ( c ‐BN), the transition metal borides (TMBs) are attractive potential superhard materials because of the network and shorter covalent bonding such as BB covalent bond and TMB bond . Diborides (TMB 2 ) and transition metal tetraborides (TMB 4 ) have been widely investigated over the last years .…”
Section: Introductionmentioning
confidence: 99%
“…Hard and superhard materials (≥40 GPa) are very important industrial materials, which are widely used in various industrial applications because of their high hardness, ultracompressibility, high melting point, and excellent thermal stability etc . In comparison to diamond and boron nitride ( c ‐BN), the transition metal borides (TMBs) are attractive potential superhard materials because of the network and shorter covalent bonding such as BB covalent bond and TMB bond . Diborides (TMB 2 ) and transition metal tetraborides (TMB 4 ) have been widely investigated over the last years .…”
Section: Introductionmentioning
confidence: 99%
“…Compared to diamond and boron nitride superhard materials, transition metal borides (TMBs) are attractive superhard materials because of their fascinating mechanical, electronic and thermodynamic properties etc. [1][2][3][4][5][6][7][8][9] However, hardness is a complex phenomenon, which is related to the structural conguration, chemical bonding, electronic structure, deformation, defects, etc. [10][11][12][13][14] For TMBs superhard materials, previous work has shown that the Vickers hardness is determined by the network and shorter B-B covalent bonds.…”
Section: Introductionmentioning
confidence: 99%
“…47 ture of 1600-1800°C. 48 Some borides, including WB 3 , 49 MnB, 50 Mn 3 B 4 , 51 and MoB 4 , 52 were also synthesized successively with a high pressure and high temperature method. In addition, Fokwa's group employed the arc-melting procedures to prepare several Mo-B phases (i.e., Mo 2 B, α-MoB, β-MoB, and α-MoB 2 ), containing about 10% weight percentage of impurity phases.…”
Section: Element Reaction Routementioning
confidence: 99%